THE INFLUENCE OF POPULATION GROWTH, INFLATION AND HUMAN DEVELOPMENT INDEX ON ECONOMIC GROWTH AND POVERTY - Satria, Wisnu; Fachrurrozi, Kamal; Kadri , Mirzatul; Mubarak, Muhammad Syahrul (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
This study aims to analyze and find out the influence of population growth inflation and the human development index on economic growth and the number of poor people in East Kalimantan Province. The analysis tool used is path analysis. The data used is secondary data from 2013-2022. The results of the analysis of path 1. Population growth has a positive and insignificant effect on economic growth, inflation has a negative and insignificant effect on economic growth, and the human development index has a positive and significant effect on economic growth in East Kalimantan Province. The results of the analysis of path 2. Population growth negatively and significantly affects the number of poor people, inflation has a positive and insignificant effect, and the human development index negatively and significantly affects the number of poor people, as well as economic growth, has a positive and significant effect on the number of poor people in East Kalimantan Province. Population growth and the human development index have a positive and insignificant effect on the number of poor people through economic growth, while inflation has a negative and insignificant effect on the number of poor people through economic growth in East Kalimantan Province. The effect of total inflation and economic growth is positive and un-negating on the number of poor people, population growth and human development index are negative and insignificant on the number of poor people in East Kalimantan Province.